Acetylation and cleavage of purine nucleosides. Synthesis of 6-azauridine, 5-fluorouridine, and 5-methyluridine. - Beránek, J (1976)
Inosine (I) when acetylated with acetic anhydride in the presence of acetyl chloride in acetic acid solution (the so called "acid acetylation"), affords an acetylated nucleoside III (75%) along with cleavage products of the nucleoside (hypoxanthine, 19%). The reaction of I with acetyl chloride (7 days) results in the formation of hypoxanthine (95%) and triacetylribofuranosyl chloride (IV) isolated in the form of tetraacetylribofuranose (47%). The acetylated purine nucleoside affords a similar result by reaction with acetyl chloride or acetyl bromide. 2'-Deoxyuridine gives a diacetyl derivative (80%) by reaction with acetyl bromide. On treatment with acetyl bromide, the nucleoside bond of purine nucleosides is quantitatively cleavaged (4 h, 20 degrees C) with the formation of tri-O-acetyl-D-ribofuranosyl bromide (X). The halogenose X affords pure beta-anomers, namely, 1,2,3,5-tetra-O-acetyl-beta-D-ribofuranose (75%), the triacetyl derivatives of 5-methyluridine (XVIIa; 75%, referred to guanosine), 6-azauridine (XVIII; 71%), and 5-fluorouridine (XIXa; 75%).